Orchestrating Relevance – Critique of a Questionable Trait of Modern Science Communication - Antonio Togni (CHIMIA)
This essay critically analyzes the widespread phenomenon of claiming relevance when reporting original research. Specific examples from an area of method development in organofluorine chemistry demonstrate that the pursuit of worthiness of the corresponding research is mainly justified by putting forward a broad general industrial context that could potentially benefit in form of applications. However, it is deliberately ignored that such applications are in the vast majority of cases highly improbable or objectively unrealistic. Notwithstanding that scientists are nowadays often explicitly forced to orchestrate relevance, be it by researchfinancing institutions and/or journals’ reviewers, it is argued that this is, from the point of view of research ethics at least, problematic.